Joint care can outweigh costs of nonkin competition in communal breeders. (20th October 2017) - Bebbington, Kat; Fairfield, Eleanor A; Spurgin, Lewis G; Kingma, Sjouke A; Dugdale, Hannah; Komdeur, Jan; Richardson, David S
Abstract : Parents who raise their nestling in a communal nest alongside the nestling of other parents can reduce costly competition between offspring by providing more food. In the Seychelles warbler, we show that nestlings raised with a sibling have lower mass and survival than those raised alone, whereas nestlings raised with a nonsibling do not suffer these costs. Our results suggest that increased food provisioning can reduce competition among nonsiblings and facilitate the evolution of joint-nesting. Abstract: Competition between offspring can greatly influence offspring fitness and parental investment decisions, especially in communal breeders where unrelated competitors have less incentive to concede resources. Given the potential for escalated conflict, it remains unclear what mechanisms facilitate the evolution of communal breeding among unrelated females. Resolving this question requires simultaneous consideration of offspring in noncommunal and communal nurseries, but such comparisons are missing. In the Seychelles warbler Acrocephalus sechellensis, we compare nestling pairs from communal nests (2 mothers) and noncommunal nests (1 mother) with singleton nestlings. Our results indicate that increased provisioning rate can act as a mechanism to mitigate the costs of offspring rivalry among nonkin. Increased provisioning in communal broods, as a consequence of having 2 female parents, mitigates any elevated costs of offspring rivalry among nonkin: per-capita provisioning and survival was equal in communal broods and singletons, but lower in noncommunal broods. Individual offspring costs were also more divergent in noncommunal broods, likely because resource limitation exacerbates differences in competitive ability between nestlings. It is typically assumed that offspring rivalry among nonkin will be more costly because offspring are not driven by kin selection to concede resources to their competitors. Our findings are correlational and require further corroboration, but may help explain the evolutionary maintenance of communal breeding by providing a mechanism by which communal breeders can avoid these costs.